Impact Tourism on off Farm Business and Employment Opportunities in Coastal Area - Widya Setiyanti, Dian; Sadono, Dwi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
The tourism has a very significant role in national economic development. Social changes occured as a result of direct contacts from tourism in tourist areas. One of consequence from the tourism activities is emergence of businesses and employment opportunities which can encourage local economies. The purpose of this research was to identify business and employment opportunities as a result of tourism activities at Pramuka Island and also to identify characteristics of the community. Another purpose is to analyze level of income, linkages between agricultural sector and nonagriculture sector, and transfer of resources (land) that arise due to tourism activities. The research methods are qualitative method which supported by quantitative methods. The results showed that tourism activities in Pramuka island has created business and employment opportunities for local community. Opportunities are predominantly used by natives. Tourism businesses and employment tend to be main livelihood of local people although their income are still at low-income levels. Linkage between agriculture sector and nonagriculture sector in Pramuka Island is shown by the increasing demand in fisheries sector as raw material for some businesses. Transfer of resources tends to occur among natives and there is one policy that prohibits people to build a building around the island ring road. Keywords : impact, tourism, business and employment opportunities.